High diversity of Salmonella spp. from children with diarrhea, food, and environmental sources in Kilimanjaro – Tanzania: one health approach - Hugho, Ephrasia A.; Kumburu, Happiness H.; Thomas, Kate; Lukambagire, AbdulHamid S.; Wadugu, Boaz; Amani, Nelson; Kinabo, Grace; Hald, Tine; Mmbaga, Blandina T. (Frontiers in Microbiology, 2024)
Salmonella is one of the most frequent causes of diarrhea globally. This study used a One Health approach to identify Salmonella species in children admitted with diarrhea and tested samples from the cases' household environment to investigate their genetic similarity using whole genome sequencing. Surveillance of hospitalized diarrhea cases among children under five years was conducted in rural and urban Moshi Districts in the Kilimanjaro Region of Tanzania from July 2020 through November 2022. Household visits were conducted for every child case whose parent/caregiver provided consent. Stool samples, water, domestic animal feces, meat, and milk were collected and tested for Salmonella. Isolates were sequenced on the Illumina NextSeq platform. Multilocus Sequence Typing and phylogenetic analyses were performed to map the genetic relatedness of the isolates. Salmonella was isolated from 72 (6.0%) of 1191 samples. The prevalence of Salmonella in children with diarrhea, domestic animal feces, food, and water was 2.6% (n=8/306), 4.6% (n=8/174), 4.2% (n=16/382), and 17.3% (n=39/225), respectively. Four (1.3%) of the 306 enrolled children had a Salmonella positive sample taken from their household. The common sequence types (STs) were ST1208, ST309, ST166, and ST473. Salmonella Newport was shared by a case and a raw milk sample taken from the same household. The study revealed a high diversity of Salmonella sppspp., however, we detected a Salmonella clone of ST1208 isolated at least from all types of samples. These findings contribute to understanding the epidemiology of Salmonella in the region and provide insight into potential control of foodborne diseases through a One Health approach.